2010
DOI: 10.2189/asqu.2010.55.3.439
|View full text |Cite
|
Sign up to set email alerts
|

How New Market Categories Emerge: Temporal Dynamics of Legitimacy, Identity, and Entrepreneurship in Satellite Radio, 1990–2005

Abstract: We theorize how new market categories emerge and are legitimated through a confluence of factors internal to the category (entrepreneurial ventures) and external to the category (interested audiences). Using qualitative and quantitative analyses and multiple data sources overtime, we study the evolution of the U.S. satellite radio market over its initial sixteen years. We offer convergent evidence to show that the legitimation of a new market category precipitates shifts in the focus of market actors' attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
810
2
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 718 publications
(856 citation statements)
references
References 79 publications
13
810
2
8
Order By: Relevance
“…Recent research on conflicting institutional logics, especially in the context of emerging fields, provides a case in point (Navis andGlynn 2010, Purdy andGray 2009). This research suggests that in such fields, institutional arrangements themselves can exhibit considerable levels of uncertainty.…”
Section: Implications For Institutional Theorymentioning
confidence: 99%
“…Recent research on conflicting institutional logics, especially in the context of emerging fields, provides a case in point (Navis andGlynn 2010, Purdy andGray 2009). This research suggests that in such fields, institutional arrangements themselves can exhibit considerable levels of uncertainty.…”
Section: Implications For Institutional Theorymentioning
confidence: 99%
“…Increased organizational density within a sector contributes to overcoming the liability of newness and increasing legitimacy (Carroll and Hannan, 1989;Hannan et al, 1995;McKendrick and Carroll, 2001): "density is a parsimonious indicator of legitimacy that enjoys predictability for a remarkably wide array of organizations" (Deephouse and Suchman, 2008, p. 55). Density alone, however, is not enough to secure legitimacy; the public must have knowledge of the organizations and be able to recognize and categorize them (Hsu and Hannan, 2005;McKendrick et al, 2003;Navis and Glynn, 2010). Prior studies have found that organizations engage in strategies to increase public recognition and gain legitimacy (for example, Suchman, 1995;Scherer et al, 2013;Tornikoski and Newbert, 2007;Zimmerman and Zeitz, 2002).…”
Section: Legitimation Strategiesmentioning
confidence: 99%
“…Organizations attempting to create new organizational forms assert a set of core features that differs from that of existing forms (Navis & Glynn, 2010), and thus face the challenge of incompatibility with the institutional rules dominant in existing fields (Aldrich & Fiol, 1994). While founders may possess clear visions for their organizations, the realization of their plans is conditional on the approval of powerful actors in the new organization's environment.…”
Section: Senior Leadership Teams In Hybrid Organizationsmentioning
confidence: 99%